Associations Between Aromatic Compounds and Hepatorenal Biomarkers Among Coking Workers: Insights from Mediation Analysis - Dongming Chen; Hang Yu; Hailing Li; Guiying Li; Taicheng An (Toxics)
Coking activities produce high concentrations of aromatic compounds (ACs) and related substances, which may have impacts on human health. However, the health effects of these substances on humans exposed to coking sites have not been fully elucidated. A total of 637 people were recruited to participate in this cross-sectional study. Using multiple linear regression and Bayesian kernel machine regression, we investigated the relationships between the urinary parent or metabolite forms of ACs (including metabolites of PAHs and their derivatives, nitrophenols, and chlorophenols) and hepatorenal biomarkers (HRBs), including total bilirubin, aspartate aminotransferase/alanine aminotransferase, serum uric acid, creatinine, albumin/globulin, and urea. The HRBs adopted in this study can effectively represent the status of human liver and kidney function. Mediation analysis was performed to investigate the possible mediating relationship between ACs and HRBs using oxidative stress markers as mediators. Our study indicated that ACs were significantly associated with increases in TBIL, AST/ALT, A/G, and UA, as well as a significant decrease in Cr. UREA showed no association with ACs among coking workers. The oxidative stress markers 8-hydroxy-2’-deoxyguanosine, 8-iso-prostaglandin-F2α, and 8-iso,15(R)-prostaglandinF2α mediated the induction of ACs on TBIL. Our results suggest that AC exposure in coking workers may be associated with adverse changes in hepatorenal biomarkers. This study highlights the significant impact of ACs from coking activities on workers’ hepatorenal biomarkers, providing crucial evidence for health risk assessment and prevention in affected populations.